Smart grids, smart users? The role of the user in demand side management - Goulden, Murray; Bedwell, Benjamin D.; Rennick-Egglestone, Stefan; Rodden, Tom; Spence, Alexa (Elsevier, 2014)
Smart grids are a key feature of future energy scenarios, with the overarching goal of better aligning energy generation and demand. The work presented here considers the role of the user in such systems, and the contexts in which such roles might emerge. The data used is drawn from focus groups with 72 participants, using novel scenario techniques to contextualise smart grid technologies in domestic settings. Two contrasting visions of the smart grid are presented, a centralised system based on current institutional arrangements, and an alternative system in which decentralisation of generation and control is pursued. Using the concepts of ‘energy consumer’ and ‘energy citizen’, the paper considers what forms of engagement are likely to be generated by the two visions. We propose that smart grid designs must look beyond simply the technology and recognise that a smart user who is actively engaged with energy is critical to much of what is proposed by demand side management. We conclude that the energy citizen holds out most promise in this regard. The implications of this for policy makers are discussed.